Tailoring biomaterials and applications targeting tumor-associated macrophages in cancers - Jing, Fangqi; Liu, Xiaowei; Chen, Xiaoxuan; Wu, Fanglong; Gao, Qinghong (Frontiers in Immunology, 2022)
Tumor-associated macrophages (TAMs) play a critical role in supporting tumor growth and metastasis, taming host immunosurveillance, and augmenting therapeutic resistance. As the current treatment paradigms for cancers are generally insufficient to exterminate cancer cells, anti-cancer therapeutic strategies targeting TAMs have been developed. Since TAMs are highly heterogeneous and the pro-tumoral functions are mediated by phenotypes with canonical surface markers, TAM-associated materials exert anti-tumor functions by either inhibiting polarization to the pro-tumoral phenotype or decreasing the abundance of TAMs. Furthermore, TAMs in association with the immunosuppressive tumor microenvironment (TME) and tumor immunity have been extensively exploited in mounting evidence, and could act as carriers or accessory cells of anti-tumor biomaterials. Recently, a variety of TAM-based materials with the capacity to target and eliminate cancer cells have been increasingly developed for basic research and clinical practice. As various TAM-based biomaterials, including antibodies, nanoparticles, RNAs, etc., have been shown to have potential anti-tumor effects reversing the TME, in this review, we systematically summarize the current studies to fully interpret the specific properties and various effects of TAM-related biomaterials, highlighting the potential clinical applications of targeting the crosstalk among TAMs, tumor cells, and immune cells in anti-cancer therapy.